Characteristics and clinical management of patients admitted to cholera wards in a regional referral hospital during the 2012 epidemic in Sierra Leone - Alexander Blacklock; Andrew Sesay; Abdul Kamara; Mamud Kamara; Claire Blacklock (Taylor & Francis Group, 2015)
Background and objectives: In 2012, Sierra Leone suffered a nationwide cholera epidemic which affected the capital Freetown and also the provinces. This study aims to describe the characteristics and clinical management of patients admitted to cholera isolation wards of the main referral hospital in the Northern Province and compare management with standard guidelines. Design: All available clinical records of patients from the cholera isolation wards were reviewed retrospectively. There was no active case finding. The following data were collected from the clinical records after patients had left the ward: date of admission, demographics, symptoms, dehydration status, diagnoses, tests and treatments given, length of stay, and outcomes. Results: A total of 798 patients were admitted, of whom 443 (55.5%) were female. There were 18 deaths (2.3%). Assessment of dehydration status was recorded in 517 (64.8%) of clinical records. An alternative or additional diagnosis was made for 214 patients (26.8%). Intravenous (IV) fluids were prescribed to 767 patients (96.1%), including 95% of 141 patients who had documentation of being not severely dehydrated. A history of vomiting was documented in 92.1% of all patients. Oral rehydration solution (ORS) was given to 629 (78.8%) patients. Doxycycline was given to 380 (47.6%) patients, erythromycin to 34 (4.3%), and other antibiotics were used on 247 occasions. Zinc was given to 209 (26.2%). Discussion: This retrospective study highlights the need for efforts to improve the quality of triage, adherence to clinical guidance, and record keeping. Conclusions: Data collection and analysis of clinical practices during an epidemic situation would enable faster identification of those areas requiring intervention and improvement.